RNA interference (RNAi): A revolutionary approach for sustainable insect pest management: RNA INTERFERENCE: A REVOLUTIONARY APPROACH FOR SUSTAINABLE INSECT PEST MANAGEMENT - SNEHA SHARMA; VISHAW DEEP SHARMA; M CHETHANKUMAR; RITTIK SARKAR; ARCHANA ANOKHE; P DURAIMURUGAN; MANOJ KUMAR YADAV (Journal of Oilseeds Research, 2026)
RNA interference (RNAi) is a naturally occurring gene regulatory mechanism present in most eukaryotic organisms and has emerged as a promising strategy for agricultural insect pest management. The process involves sequence-specific gene silencing mediated by double-stranded RNA (dsRNA) molecules that are complementary to the target messenger RNA (mRNA). In the RNAi pathway, specialized cellular enzymes recognize and cleave dsRNA into small interfering RNAs (siRNAs), which subsequently bind to the corresponding target mRNA and inhibit its expression. This suppression of essential genes disrupts vital physiological and developmental processes in insects. In recent years, extensive research has been conducted by scientific institutions, universities, and biotechnology industries to better understand the molecular mechanisms of RNAi and explore its practical applications in insect pest control. One of the major advantages of RNAi technology is its high degree of target specificity, allowing selective suppression of pest species with minimal impact on non-target organisms and beneficial insects, unlike conventional broad-spectrum chemical insecticides. Moreover, numerous studies have demonstrated the effectiveness of RNAi in inducing mortality and developmental abnormalities across various insect orders. Considering its precision, environmental safety, and potential efficacy, RNAi is regarded as a highly innovative molecular tool for sustainable and eco-friendly insect pest management.